Protein S and C4b-Binding Protein: Components Involved in the Regulation of the Protein C Anticoagulant System - Dahlbäck, Björn (Thrombosis and Haemostasis, 1991)
The protein C anticoagulant system provides important control of the blood coagulation cascade. The key protein is protein C, a vitamin K-dependent zymogen which is activated to a serine protease by the thrombin-thrombomodulin complex on endothelial cells. Activated protein C functions by degrading the phospholipid-bound coagulation factors Va and VIIIa. Protein S is a cofactor in these reactions. It is a vitamin K-dependent protein with multiple domains. From the N-terminal it contains a vitamin K-dependent domain, a thrombin-sensitive region, four EGF)epidermal growth factor (EGF)-like domains and a C-terminal region homologous to the androgen binding proteins. Three different types of post-translationally modified amino acid residues are found in protein S, 11 γ-carboxy glutamic acid residues in the vitamin K-dependent domain, a β-hydroxylated aspartic acid in the first EGF-like domain and a β-hydroxylated asparagine in each of the other three EGF-like domains. The EGF-like domains contain very high affinity calcium binding sites, and calcium plays a structural and stabilising role. The importance of the anticoagulant properties of protein S is illustrated by the high incidence of thrombo-embolic events in individuals with heterozygous deficiency. Anticoagulation may not be the sole function of protein S, since both in vivo and in vitro, it forms a high affinity non-covalent complex with one of the regulatory proteins in the complement system, the C4b-binding protein (C4BP). The complexed form of protein S has no APC cofactor function. C4BP is a high molecular weight multimeric protein with a unique octopus-like structure. It is composed of seven identical α-chains and one β-chain. The α-and β-chains are linked by disulphide bridges. The cDNA cloning of the β-chain showed the α- and β-chains to be homologous and of common evolutionary origin. Both subunits are composed of multiple 60 amino acid long repeats (short complement or consensus repeats, SCR) and their genes are located in close proximity on chromosome 1, band 1q32. Available experimental data suggest the β-chain to contain the single protein S binding site on C4BP, whereas each of the α-chains contains a binding site for the complement protein, C4b. As C4BP lacking the β-chain is unable to bind protein S, the β-chain is required for protein S binding, but not for the assembly of the α-chains during biosynthesis. Protein S has a high affinity for negatively charged phospholipid membranes, and is instrumental in binding C4BP to negatively charged phospholipid. This constitutes a novel mechanism for control of the complement system on phospholipid surfaces. Recent findings have shown circulating C4BP to be involved in yet another calcium-dependent protein-protein interaction with a protein known as the serum amyloid P-component (SAP). The binding sites on C4BP for protein S and SAP are independent. SAP, which is a normal constituent in plasma and in tissue, is a so-called pentraxin being composed of 5 non-covalently bound 25 kDa subunits. It is homologous to C reactive protein (CRP) but its function is not yet known. The specific high affinity interactions between protein S, C4BP and SAP suggest the regulation of blood coagulation and that of the complement system to be closely linked.